2009
DOI: 10.1144/1354-079309-779
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic investigation of the effect of a relay ramp on simulated fluid flow: geocellular modelling of the Delicate Arch Ramp, Utah

Abstract: A fluid flow simulation study was performed to investigate potential contrasts in reservoir performance between models displaying a soft-linked relay ramp vs. models with a continuous fault. The relay ramp model is based on a well-exposed outcrop analogue -the Delicate Arch Ramp, Arches National Park, Utah. In outcrop, the relay ramp exhibits a pervasive system of cataclastic deformation bands, which were mapped and incorporated into the reservoir simulation models. Several models were simulated, using deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 47 publications
4
50
2
2
Order By: Relevance
“…We use the well detailed geomodel of the Delicate Arch Ramp in Utah made by Rotevatn et al (2009). Initial host rock properties of the sandstone are based on measurements from Antonellini and Aydin (1994): porosity 28%, horizontal permeability 1000mD and vertical permeability 100mD (Rotevatn et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We use the well detailed geomodel of the Delicate Arch Ramp in Utah made by Rotevatn et al (2009). Initial host rock properties of the sandstone are based on measurements from Antonellini and Aydin (1994): porosity 28%, horizontal permeability 1000mD and vertical permeability 100mD (Rotevatn et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…We use the well detailed geomodel of the Delicate Arch Ramp in Utah made by Rotevatn et al (2009). Initial host rock properties of the sandstone are based on measurements from Antonellini and Aydin (1994): porosity 28%, horizontal permeability 1000mD and vertical permeability 100mD (Rotevatn et al, 2009). Based on the frequency of deformation bands within each cell of the geomodel (Rotevatn et al, 2009), these petrophysical properties are modified due to faulting, as following:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the model choices (1 layer, vertically continuous deformation bands), our approach is largely two-dimensional, which is a fair approximation of flow across a network of bands confined to one geological layer (e.g. Rotevatn et al 2009). The model resulting from this semi-discrete inflated approach very closely replicates the exact geometry of the deformation band as mapped in outcrop (compare Fig.…”
Section: Incorporating the Deformation Band Network From Outcrop To Mmentioning
confidence: 99%
“…Deformation bands have, therefore, been suspected of causing production problems within siliciclastic subsurface reservoirs (Lewis & Couples 1993;Olsson et al 2004), although this has been difficult to prove given their small-scale nature. In response to this, previous studies have attempted to quantify and simulate the effect of deformation bands on fluid flow dynamics and production performance (Matthäi et al 1998;Sternlof et al 2006;Fossen & Bale 2007;Rotevatn et al 2009Rotevatn et al , 2013Rotevatn & Fossen 2011;Zuluaga et al 2016). In general these studies have demonstrated that deformation bands in siliciclastic reservoirs or aquifers may cause (i) perturbed flow patterns, leading to more tortuous fluid flow (Rotevatn et al 2009;Zuluaga et al 2016), (ii) pressure compartmentalization (Rotevatn & Fossen 2011), (iii) improved sweep efficiency (Rotevatn et al 2009;Zuluaga et al 2016), (iv) delayed water breakthrough (Rotevatn et al 2009), (v) anisotropic reservoir flow properties (Sternlof et al 2006), (vi) variable production efficiency (Sternlof et al 2006;Rotevatn et al 2009) and (vii) reduced effective permeability within the reservoir (Fossen & Bale 2007;Rotevatn et al 2013).…”
mentioning
confidence: 99%